Tantangan dan Solusi dalam Penyediaan Infrastruktur Pendidikan di Daerah Terpencil - Salsabila, Farah; Lailufar, Hauna Fathiinah; Amanatin, Ifah; Salsyabella, Ratna Cahya; Sundari, Siti Astria (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze challenges and solutions related to the provision of educational facilities and infrastructure in remote areas. This research is a literature study focused on the main theme, namely the challenges in the provision of educational facilities and infrastructure, the management of educational facilities, and the obstacles faced by remote areas, including limited infrastructure and human resources. The research stage starts from collecting, analyzing, and compiling information from various relevant literature sources, such as books, journal articles, research reports, and other related publications. The analysis is carried out descriptively by grouping information based on themes to facilitate conclusions. The results of this study propose several solutions that can be applied, including the development of basic infrastructure, the use of information technology, and the optimization of the education budget. In addition, increasing community participation, government support, and training of school managers are important steps to ensure equitable access to quality education. Collaboration between the government, the community, and the private sector is also expected to realize equitable and quality education throughout Indonesia.